Moderation des Symposiums „Förderung von Kindern mit Migrationshintergrund im Vor- und Grundschulbereich“. 20. Jahrestagung der Kommission "Grundschulforschung und Pädagogik der Primarstufe" der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE, Sektion Schulpädagogik) - Koch, Katja; Hellmich, Frank

(Mal-)Adaptives Lernverhalten von Grundschulkindern in Abhängigkeit ihrer impliziten Fähigkeitstheorien und Fähigkeitsselbstkonzepte - Hellmich, Frank

Implizite Fähigkeitstheorien, Fähigkeitsselbstkonzepte und (mal-)adaptives Lernverhalten bei Kindern im Grundschulalter. Vortrag auf der 75. Tagung der Arbeitsgruppe für Empirische Pädagogische Forschung (AEPF) - Hellmich, Frank

[Sammelrezension:] Das Hamburger Ordeelbook von 1270 samt Schiffrecht. Nach der Handschrift von Fredericus Varendorp von 1493 (Kopenhagener Codex). Textausgabe und Übersetzung ins Hochdeutsche mit rechtsgeschichtlichem Kommentar. Hrsg. von Frank Eichler. Hamburg: Mauke; Das Hamburger Ordeelbook in der Erstfassung 1270. Rechtshistorische und sprachliche Rekonstruktion aus den vorhandenen Quellen. Hrsg. von Frank Eichler. Hamburg: Mauke 2007; Die Langenbeck’sche Glosse zum Hamburger Stadtrecht von 1497. Die vollständige Glossenhandschrift von Bartholdus Eggheman von 1532 sowie Lappenbergs Auszüge aus späteren Handschriften. Hrsg. und übersetzt von Frank Eichler. Mit Einführungen von Frank Eichler und Tilman Repgen. Hamburg: Mauke 2008. - Wallmeier, Nadine (Niederdeutsches Jahrbuch)

Mihm, Magret / Mihm, Arend: Mittelalterliche Stadtrechnungen im historischen Prozess. Die älteste Duisburger Überlieferung (1348-1449). Band 1: Untersuchungen und Texte. Köln, Weimar, Wien: Böhlau 2007. Band 2: Register, Materialien, Glossar. Köln, Weimar, Wien: Böhlau 2007 - Wallmeier, Nadine (Daphnis)

Hardy spaces for the Laplacian with lower order perturbations - Luks, Tomasz (Studia Mathematica)

Multiple-Channel Detection of a Gaussian Time Series over Frequency-Flat Channels - Ramírez, D.; Vía, J.; Santamaría, I.; Scharf, L. L. (Proc.\ IEEE Int.\ Conf.\ Acoustics, Speech and Signal Process.)
This work addresses the problem of deciding whether a set of realizations of a vector-valued time series with unknown temporal correlation are spatially correlated or not. Specifically, the spatial correlation is induced by a colored source over a frequency-flat single-input multiple-output (SIMO) channel distorted by independent and identically distributed noises with temporal correlation. The generalized likelihood ratio test (GLRT) for this detection problem does not have a closed-form expression and we have to resort to numerical optimization techniques. In particular, we apply the successive convex approximations approach which relies on solving a series of convex problems that approximate the original (non-convex) one. The proposed solution resembles a power method for obtaining the dominant eigenvector of a matrix, which changes over iterations. Finally, the performance of the proposed detector is illustrated by means of computer simulations showing a great improvement over previously proposed detectors that do not fully exploit the temporal structure of the source.

Multiantenna detection under noise uncertainty and primary user’s spatial structure - Ramírez, D.; Vazquez-Vilar, G.; López-Valcarce, R.; Vía, J.; Santamaría, I. (Proc.\ IEEE Int.\ Conf.\ Acoustics, Speech and Signal Process.)
Spectrum sensing is a challenging key component of the Cognitive Radio paradigm, since primary signals must be detected in the face of noise uncertainty and at signal-to-noise ratios (SNRs) well below decodability levels. Multiantenna detectors exploit spatial independence of receiver thermal noise to boost detection performance and robustness. Here, we study the problem of detecting Gaussian signals with unknown rank-$P$ spatial covariance matrix when the noise at the receiver is independent across the antennas and with unknown power. A generic diagonal noise covariance matrix is allowed to model calibration uncertainties in the different antenna frontends. We derive the generalized likelihood ratio test (GLRT) for this detection problem. Although, in general, the corresponding statistic must be obtained by numerical means, in the low SNR regime the GLRT does admit a closed form. Numerical simulations show that the proposed asymptotic detector offers good performance even for moderate SNR values.

Multi-Sensor Beamsteering Based on the Asymptotic Likelihood for Colored Signals - Ramírez, D.; Vía, J.; Santamaría, I.; Scharf, L. L. (Proc.\ IEEE Work.\ Stat.\ Signal Process.)
In this work, we derive a maximum likelihood formula for beamsteering in a multi-sensor array. The novelty of the work is that the impinging signal and noises are wide sense stationary (WSS) time series with unknown power spectral densities, unlike in previous work that typically considers white signals. Our approach naturally provides a way of fusing frequency-dependent information to obtain a broadband beamformer. In order to obtain the compressed likelihood, it is necessary to find the maximum likelihood estimates of the unknown parameters. However, this problem turns out to be an ML estimation of a block-Toeplitz matrix, which does not have a closed-form solution. To overcome this problem, we derive the asymptotic likelihood, which is given in the frequency domain. Finally, some simulation results are presented to illustrate the performance of the proposed technique. In these simulations, it is shown that our approach presents the best results.

Capacity Region of the Two-Way Multi-Antenna Relay Channel with Analog Tx-Rx Beamforming - Lameiro, Christian; Nazábal, Alfredo; Gholam, Fouad; Vía, Javier; Santamaría, Ignacio (Proc. Int. ICST Conf. Mobile Lightweight Wireless Syst.)
In this paper we study the multiple-input multiple-output two-way relay channel (MIMO-TWRC) when the nodes use analog beamforming. Following the amplify-and-forward (AF) strategy, the problem consists of finding the transmit and receive beamformers of the nodes and the relay, and the power allocated to each one, that achieve the boundary of the capacity region. We express the optimal node beamformers in terms of the relay beamformers, and show that the capacity region can be efficiently characterized using convex optimization techniques. Numerical examples are provided to illustrate the results of this paper, and to compare the capacity region achieved by analog beamforming against the conventional MIMO schemes that operate at the baseband.

Spatial rank estimation in Cognitive Radio Networks with uncalibrated multiple antennas (invited paper) - Vazquez-Vilar, G.; Ramírez, D.; López-Valcarce, R.; Vía, J.; Santamaría, I. (Proc. Int. Conf. on Cognitive Radio and Advanced Spectrum Management)
Spectrum sensing is a key component of the Cognitive Radio paradigm. Multiantenna detectors can exploit different spatial features of primary signals in order to boost detection performance and robustness in very low signal-to-noise ratios. However, in several cases these detectors require additional information, such as the rank of the spatial covariance matrix of the received signal. In this work we study the problem of estimating this rank under Gaussianity assumption using an uncalibrated receiver, i.e. with different (unknown) noise levels at each of the antennas.

Linear precoding for time-varying MIMO channels with low-complexity receivers - Tong, Jun; Schreier, Peter J.; Weller, Steven R.; Scharf, Louis L. (Proc.\ IEEE Int.\ Conf.\ Acoustics, Speech and Signal Process.)
This paper considers linear precoding for time-varying multiple input multiple-output (MIMO) channels. We show that linear minimum mean-squared error (LMMSE) equalization based on the conjugate gradient (CG) method can result in significantly reduced complexity compared with conventional approaches. This reduction is achieved by incorporating a condition number constraint into the precoder optimization framework, which leads to clustered eigen values of the measurement covariance matrix. The cost is a small increase in MSE compared to the optimal precoder.

Experimental Evaluation of Interference Alignment Under Imperfect Channel State Information - García-Naya, J. A.; Castedo, L.; Ramírez, D.; Santamaría, I. (Proc.\ Eur.\ Signal Process.\ Conf.)
Interference Alignment (IA) has been revealed as one of the most attractive transmission techniques for the K-user in- terference channel. In this work, we employ a multiuser Multiple-Input Multiple-Output (MIMO) testbed to analyze, in realistic indoor scenarios, the impact of channel state information errors on the sum-rate performance of IA. We restrict our study to a 3-user interference network in which each user transmits a single data stream using two transmit and two receive antennas. For this MIMO interference network, only two different IA solutions exist. We also evaluate the performance gain obtained in practice by using the IA solution that maximizes the sum-rate.

Precoder design and convergence analysis of MIMO systems with Krylov subspace receivers - Tong, Jun; Schreier, Peter J.; Weller, Steven R. (Proc.\ IEEE Int.\ Symp.\ Inform.\ Theory)
This paper studies the design and analysis of large multiple-input multiple-output (MIMO) systems with linear precoding and Krylov subspace receivers. We design precoders that can improve performance with low-rank receivers. We then introduce a tool based on potential theory to analyze the convergence behavior of the mean-squared error (MSE). The effectiveness of the proposed precoder and the superexponential convergence of the MSE are demonstrated1.

Detection of rank-$P$ signals in Cognitive Radio Networks with uncalibrated multiple antennas - Ramírez, D.; Vazquez-Vilar, G.; López-Valcarce, R.; Vía, J.; Santamaría, I. (IEEE Trans.\ Signal\ Process.)
Spectrum sensing is a key component of the Cognitive Radio paradigm. Primary signals are typically detected with uncalibrated receivers at signal-to-noise ratios (SNRs) well below decodability levels. Multiantenna detectors exploit spatial independence of receiver thermal noise to boost detection performance and robustness. We study the problem of detecting a Gaussian signal with rank-$P$ unknown spatial covariance matrix in spatially uncorrelated Gaussian noise with unknown covariance using multiple antennas. The generalized likelihood ratio test (GLRT) is derived for two scenarios. In the first one, the noises at all antennas are assumed to have the same (unknown) variance, whereas in the second, a generic diagonal noise covariance matrix is allowed in order to accommodate calibration uncertainties in the different antenna frontends. In the latter case, the GLRT statistic must be obtained numerically, for which an efficient method is presented. Furthermore, for asymptotically low SNR, it is shown that the GLRT does admit a closed form, and the resulting detector performs well in practice. Extensions are presented in order to account for unknown temporal correlation in both signal and noise, as well as frequency-selective channels.

Frequency-Domain Methodology for Measuring MIMO Channels Using a Generic Test Bed - Gutiérrez, J.; Pérez, J.; Ramírez, D.; Vielva, L.; Ibáñez, J.; Santamaría, I. (IEEE Trans. Instrum. Meas.)
A multiple-input multiple-output (MIMO) frequency-domain channel measurement methodology is pre- sented. This methodology can be implemented in any transmit/receive hardware consisting of radio frequency modules and baseband digital processing units. It involves the transmission and reception of frequency and phase-optimized complex exponentials through antenna arrays, followed by an offline frequency estimation, which makes additional synchronization circuitry unnecesary. To test the feasibility of this method, a series of measurements is presented, employing a $4 × 4$ dual-band (2.4/5 GHz) MIMO test bed.

Experimental Validation of Interference Alignment Techniques using a Multiuser MIMO Testbed - Ramírez, D.; Santamaría, I.; García-Naya, J. A.; Castedo, L. (Proc. Int. ITG Work. on Smart Antennas)
Hardware platforms and testbeds are an essential tool to evaluate, in realistic scenarios, the performance of wireless communications systems. In this work we present a multiuser Multiple-Input Multiple-Output (MIMO) testbed made up of 6 nodes, each one with 4 antennas, which allows us to evaluate Interference Alignment (IA) techniques in indoor scenarios. We specifically study the performance of IA for the 3-user interference channel in the 5 GHz band. Our analysis identifies the main practical issues that potentially degrade the IA performance such as channel estimation errors or collinearity between the desired signal and interference subspaces.

Locally stationary harmonizable complex improper stochastic processes - Wahlberg, Patrik; Schreier, Peter J. (J.\ Time Ser.\ Anal.)

Complex-Valued Signal Processing: The Proper Way to Deal With Impropriety - Adali, Tülay; Schreier, Peter J.; Scharf, Louis L. (IEEE Trans.\ Signal\ Process.)

Stability verification for monotone systems using homotopy algorithms - Rüffer, B. S.; Wirth, Fabian R. (Numer. Algorithms)